مصادر شریعت کی تفہیم جدید : علامہ اقبال کے افکار کا مطالعہ (Al-Qamar, 2023)
Human life is composed of stability and fluidity. Allah has made stability and change an essential part of this system of the universe. Therefore, the best life and the best system will be the one in which these two elements are present. A system which is not fundamentally stable and does not subtly accept change can never be amenable and permanent to human beings like if the universe were always the same color, the weather always the same, the day always the same. If there is day or night, this universe will become dull because the beauty of this universe is due to the changes and changes within it in view of this code, if we look at the Islamic system, we can see a clear difference between the early period of Islam and today's period, that is, the first four centuries were based on the same principle that in each period, the basic sources of sharīʿah were based on the circumstances. It used to be read in perspective, but then the Ummah became stagnant and the research done centuries ago was considered as the final word, due to which apparently sharīʿah and Islamic law started to look far behind the speed of time. Dr. Muhammad Iqbal was among those who realized this disturbing situation, so he emphasized on the modern understanding of the sources of Sharīʿah so that the Ummah could move out of decline and move towards the path of prosperity. In this paper, we will present a research review of Dr. Muhammad Iqbal's thoughts of a modern understanding of the sources of Sharīʿah.
Keywords: Sharia; Iqbal; stability; fluidity; universe